Sorafenib for the treatment of hepatocellular carcinoma - Hanžel, Jurij (Radiology and oncology (Ljubljana), 2020)
Background Sorafenib is an oral multi-kinase inhibitor used for the treatment of hepatocellular carcinoma. Its efficacy in randomised controlled trials was demonstrated in patients with well-preserved liver function and good functional status. In the real-world setting, treatment is often offered to patients outside these criteria. We therefore performed a single-centre real-world cohort study on the efficacy of sorafenib in patients with hepatocellular carcinoma. Patients and methods We identified all patients with hepatocellular carcinoma initiating treatment with sorafenib between January 2015 and January 2018. The primary endpoint was overall survival (OS) since starting sorafenib. Clinical and demographic variables associated with survival were studied. Results The median OS was 13.4 months (95% CI 8.2%18.6). Multivariable Cox%s regression identified worse ECOG performance status (HR 2.21; 95% CI 1.56%3.16; P < 0.0001), Child-Pugh class C (HR 52.4; 95% CI 3.20%859; P = 0.005) and absence of prior locoregional treatment (HR 2.30; 95% CI 1.37%3.86; P = 0.002) to be associated with increased mortality. Conclusions Careful selection of patients for treatment with sorafenib is of paramount importance to optimize outcomes.
Keywords: hepatocelularni karcinom; preživetje; sorafenib